Pemberdayaan Berbasis Komunitas Untuk Mewujudkan Sumber Daya Manusia Unggul - Lubis, Dewi Shinta Wulandari; Sulaiman, Fahmi; Nurhayati; Nasution, Wendi Amsuri; Mubarak, Husni; Juli Isnaini, Dewi Budhiartini (Jurnal Masyarakat Indonesia (Jumas), 2025)
Community capacity building is a strategic element in creating superior human resources (HR) that are competitive in the global era. This article discusses the approach to strengthening community capacity through lecture methods, socialization, and cleaning activities in the Al-Qur'an Memorizer Village, Mekar Jaya Village, Sei Bingei District, Langkat Regency. The results of the activities show an increase in understanding, active community participation, and the growth of collective awareness in village development based on religious values. This activity strengthens the foundation of the character of religious, productive, and environmentally aware HR.